Projection of future temperature-related mortality due to climate and demographic changes. (September 2016) - Lee, Jae Young; Kim, Ho
Abstract: Understanding the effects of global climate change from both environmental and human health perspectives has gained great importance. Particularly, studies on the direct effect of temperature increase on future mortality have been conducted. However, few of those studies considered population changes, and although the world population is rapidly aging, no previous study considered the effect of society aging. Here we present a projection of future temperature-related mortality due to both climate and demographic changes in seven major cities of South Korea, a fast aging country, until 2100; we used the HadGEM3-RA model under four Representative Concentration Pathway (RCP) scenarios (RCP 2.6, 4.5, 6.0, and 8.5) and the United Nations world population prospects under three fertility scenarios (high, medium, and low). The results showed markedly increased mortality in the elderly group, significantly increasing the overall future mortality. In 2090s, South Korea could experience a four- to six-time increase in temperature-related mortality compared to that during 1992–2010 under four different RCP scenarios and three different fertility variants, while the mortality is estimated to increase only by 0.5 to 1.5 times assuming no population aging. Therefore, not considering population aging may significantly underestimate temperature risks. Highlights: Temperature-related mortality due to climate and demographic changes was projected. This is first to show how society aging affects future temperature-related mortality. Elderly group is more vulnerable to climate changes than other population groups. Temperature-related mortality in South Korea increases up to six times in the 2090s.